Knowledge, attitudes, and practices of dentists in the Parañaque dental chapter regarding the management of patients with special health care needs - Laforteza, Denys Angeli P.; Mallari, Roselle Marie H.; Reyes, Louise Marie R.; Tan, Liza Maxine Kimberly G.; Alfaro, Arlene Cecilia A. (Manila Department of Community Dentistry, University of the Philippines Manila, 2018)
INTRODUCTION: In the Philippines, around 1.44 million households include persons with special health care needs (SHCN). Metro Manila alone has around 167,000 individuals with a disability, most of whom are unable to access dental services. The objective of the study was to determine the knowledge, attitudes and practices of dentists in the Parañaque Dental Chapter regarding the management of patients with special health care needs.
METHODS: A cross-sectional descriptive study design utilizing a total enumeration sampling design was employed to establish baseline data. Sixty-three respondents accomplished a 4-page questionnaire during a seminar in Max's Restaurant, Sucat, Parañaque City last September 19, 2018.
RESULTS: Majority had been practicing for over 10 years (82.5%), and had specializations (67.6%). Most had encountered (89%) and treated patients with SHCN (87.3%).Examinations, scaling and polishing, and restorative treatments were the most commonly done. Overall, 92.1% had adequate knowledge, but 57.6% claimed not to feel competent enough. All reported that treating such patients can be fulfilling, with 95% expressing the desire to attend future seminars on the management of patients with special health care needs.
CONCLUSIONS: It can be surmised that the respondents had adequate knowledge. Those who had treated such patients were able to employ behavioral management techniques. The respondents displayed an overall positive attitude and were receptive towards further learning and experience.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Yes
Keywords: Oral health; Pediatric dentistry; Patient management